A comparison of enameloplasty sealant technique with conventional sealant technique: A scanning electron microscope study - Khanna R; Pandey R; Singh N; Agarwal A (Wolters Kluwer Medknow Publications, 2009)
Context: An accurate diagnosis of occlusal surface of permanent posterior teeth for the presence of caries is a challenge to the clinician, when using traditional explorer. This dilemma of hidden caries has led to invasively opening of the fissure before sealant placement. Enameloplasty is one such invasive procedure that has been implicated in the successful application of pit and fissure sealants. Aims: The present study aims at evaluating the fissure micromorphology and sealant penetration under scanning electron microscope both with conventional sealant technique and enameloplasty sealant technique. Settings and Design: The study comprised of extracted human posterior teeth subjected to enameloplasty of the fissures in the study groups as compared to unprepared fissures in the control groups. Materials and Methods: The enameloplasty was performed with the help of specially designed Fissurotomy bur. The sealant used was Clinpro from 3M. All the samples were prepared for examination under scanning electron microscope. Statistical Analysis: A student ′t′ test was performed to compare the study and the control groups. Results: (i) The surface area available for sealant placement on the occlusal surface was significantly increased following enameloplasty. (ii) Fissure width following enameloplasty was significantly increased. (iii) Extent of sealant penetration was significantly greater with enameloplasty sealant technique as compared to conventional sealant. Conclusion: Enameloplasty sealant technique can be preferred to conventional sealant technique for improving adhesion, adaptation and penetration of the sealant within the fissure system.